Вплив добрив на продуктивність сої різних груп стиглості в умовах Степу України - Бридун, Олександр Сергійович; Brydun, Oleksandr (ЦНТУ, 2024)
В даній випускній кваліфікаційній роботі вивчено ефективність обробки насіння добривом Рост-Форте для сортів сої різних груп стиглості. Мета досліджень – встановити ефективність застосування добрив для обробки насіння сої різних груп стиглості. В умовах Степу України слід проводити обробку насіння органо-мінеральним добривом Рост-Форте, що забезпечить прибавку врожаю сортів Самородок та Діадема Поділля 1,1 ц/га, сорту Азимут – 1,3 ц/га. In this final qualification work, the efficiency of seed treatment with Rost-Forte fertilizer for soybean varieties of different maturity groups was studied. The purpose of research is to establish the effectiveness of fertilizer application for processing soybean seeds of different maturity groups. In the conditions of the Steppe of Ukraine, seed treatment with Rost-Forte organic-mineral fertilizer should be carried out, which will ensure an increase in the yield of the Samorodok and Diadem Podillya varieties by 1.1 с/ha, and the Azimut variety by 1.3 с/ha.
Effect of fertilizers on soybean productivity of different maturity groups in the Steppe
Keywords: соя; добрива; урожайність; soybeans; fertilizers; productivity